Investigation of optimal concentration of QDs on the performance of QD-based luminescent solar concentrators - Faysal, Atik; Nahar, Mst Tajmun; Nawar, Nafiu; Kaysir, Md Rejvi; Jahirul Islam, Md Jahirul (Institute of Electrical and Electronics Engineers Inc., 2020)
Luminescent solar concentrators (LSCs) offer a cost-effective alternative of harvesting the conventional concentrated solar energy. It uses fluorescent materials embedded in an optical waveguide to absorb, reemit, and concentrate incident solar irradiance to the edges of the waveguide, where small Photovoltaic (PV) cells are attached. Quantum dot (QD) is a good candidate as luminophores for LSCs as it shows a larger Stokes shift, which helps to reduce the dominant reabsorption loss. Here, an effective Monte Carlo ray-tracing simulation model is developed incorporating all loss mechanisms of LSCs to study the optimal concentration of QDs for a given LSC structure that provides the maximum optical efficiency. Three different QDs (CuInS2, AgInS2/ZnS, and ClSeS/ZnS) are employed here to investigate the optimal concentration of the 10cm*15cm*0.3cm LSC system. Among the QDs investigated here, the AgInS2/ZnS QD-based LSC shows the highest efficiency of 2.545% at the concentration of 200 ppm. This study helps to identify the optimal optical concentration of QDs for improving the optical efficiency of QD-based LSCs.